Poetry Sycophants and the Authority [On Grovelling to Pavelić, Tito and Tuđman] - Sorel, Sanjin (Poznańskie Studia Slawistyczne, 2019)
In the analysis of Croatian political poetry, although the article speaks only about texts on the subject of Ante Pavelić, Josip Broz - Tito and Franjo Tuđman, I also refer to all those who have written or are still writing sycophant texts, somewhere on the margins of good taste and obsequious poems. Works about the mentioned historical figures are just a name, a sign of the ideology represented by: fascism, socialism, nationalism (spiritual renewal). The analysis comprises the following topics: apotheosis, mythological narratives, government and social authority, revisionism. The name-induced conflict on the social scene is purely symbolic and future-oriented, but also deals with values that will determine the re/presentation of the Republic of Croatia.